The Impact of Parkinson's Disease on General and Specific Motor Aptitudes: A Study of Older Brazilian Adults. Issue 2 (April 2022) - Andreis, Lucia M.; Mariano, Marilia; Silva, Lorenna W. L.; Bianco, Claudia D.; Rosa Neto, Francisco
This study investigated motor aptitude in older adults with and without Parkinson's disease (PD) to further specify known motor-related changes of PD. We divided 671 older adults (23.5% male; M age = 69.6, SD = 6.6 years) into a Parkinson's Disease Group (PDG) and a non-Parkinson's Disease Group (NPG) and assessed their general motor aptitude (GMA) and their specific motor aptitudes (in Coordinative, Proprioceptive, and Perceptive domains) using the Motor Scale for Older Adults. We used the chi-squared tests and logistic regression to identify and affirm an associations between PD and motor aptitude, we found that most adults without PD showed normal motor aptitude (GMA: 80.7%; Proprioceptive: 82.3%; Perceptive: 81.4%) except for the Coordinative skills, for which 56.4% of these participants had motor impairment. Most partipants with PD showed motor impairments (GMA: 94.7%; Coordinative: 97.4%; Proprioceptive: 97.4%), except in the Perceptive domain, for which 68.4% of participants with PD showed normal aptitude. There were significant associations between PD and GMA (OR = 127.6), Coordinative motor skills (OR = 48.0), and Proprioceptive skills (OR = 204.4), even after the model was adjusted for gender and age. Our use of the Motor Scale for Older Adults in contrasting groups of older Brazilian adults provides further specificity to the motor aptitude characteristics of older adults with PD.